A CONTRASTIVE ANALYSIS OF SIMPLE SENTENCES IN ENGLISH AND JAVANESE LANGUAGE - Fitriyani Fitriyani; D.P. Ramendra; I.W. Swandana (Universitas Pendidikan Ganesha, 2018)
This research studied about English and Javanese simple sentences which aimed to find the similarities and differences between English simple sentences and Javanese language. This study is descriptive qualitative research that applied contrastive analysis as the methodology. The data were taken from English textbooks and Javanese magazines. The results of this study showed there were similarities and differences in English and Javanese language simple sentences. The similarities were (1) some of simple sentence have similar patterns were SP for verbal sentence and SPO patterns. (2) the major elements were subject and predicator. The differences were (1) Javanese language had SP pattern for nominal, adjectival, prepositional, and numeral sentence. While in English there was no pattern. (2) In English, predicator must be in verb phrase: auxiliary verbs, linking verbs, or action verbs. However, In Javanese language, the predicator of a sentence might be in verb phrase, adjectival phrase, and prepositional phrase.